2018
DOI: 10.1002/oby.22196
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options for Severe Obesity in the Pediatric Population: Current Limitations and Future Opportunities

Abstract: Treating pediatric severe obesity effectively and safely is extremely challenging. Some progress has been made, but substantially more effort and innovation are needed in the future to combat this serious and ongoing medical and public health issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 101 publications
1
47
0
1
Order By: Relevance
“…Severe obesity is present in 5% of children ages 2 to 19 years and is very common among children seeking care for obesity . Tertiary interventions, such as bariatric surgery and some weight control medications, are approved for adolescents but not pre‐adolescents with severe obesity despite similar prevalence rates . Behavior‐based, nonresidential interventions that report specifically on outcomes of children with severe obesity are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Severe obesity is present in 5% of children ages 2 to 19 years and is very common among children seeking care for obesity . Tertiary interventions, such as bariatric surgery and some weight control medications, are approved for adolescents but not pre‐adolescents with severe obesity despite similar prevalence rates . Behavior‐based, nonresidential interventions that report specifically on outcomes of children with severe obesity are limited.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 36 studies were found that met the search criteria. The majority of studies were reviews ( n = 16, Table ), 8 were observational, 7 were case‐control studies, 3 were quasi‐experimental/case‐control studies, and 2 were RCTs (1 was a methods paper only) (Table ). No studies that tested the combination of pharmacotherapy interventions with MBS were found.…”
Section: Resultsmentioning
confidence: 99%
“…Other reviews included the importance of the preoperative assessment tools and postoperative multidisciplinary teams (e.g., dietitian, social worker, psychologist) , clinical dietary recommendations , and cosmetic (e.g., skin) considerations, but none did so in a theoretical framework or by citing evidence‐based findings from previously successful secondary prevention lifestyle interventions. The three review papers that included pharmacotherapy support interventions highlighted the need for more research focused on combination therapies (MBS, pharmacotherapy, lifestyle) to support precision medicine treatment approaches among adolescents with severe obesity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study designs for lifestyle treatments vary greatly, but regardless of the setting or methodology, they only show a modest effect on long-term weight loss. [3][4][5][6] In addition, it is well documented that children with overweight and obesity have more comorbidities, such as dyslipidaemia, high blood pressure, abnormalities in left ventricular mass or function, abnormalities in endothelial function, hyperinsulinaemia, and insulin resistance compared to children with normal weight. 7 They also present with poorer psychological health and are at increased risk of becoming adults with overweight or obesity when compared to their normal-weight counterparts.…”
Section: Introductionmentioning
confidence: 99%